Spawning season and food habits of Metapenaeus ensis in the Marudu Bay, Sabah - Jamal, Izzati (2013)
Study on the spawning period of penaeid prawns, M. ensis was conducted from December 2012 to September 2013. The objectives of the study are estimate the spawning period, food habit of M.ensis. To clarify the food habits of Metapenaeus ensis, the gut content of M.ensis samples was collected in the Marudu Bay Sabah, examined the stomach content of 200 specimens collected monthly using gill nets and three layer nets. Each M.ensis sample was dissected to collect the male, female gonad and stomach. The spawning period of M.ensis was estimate started in February to April and July to August with higher GSI value in September (3.56%) and lowest spawning season in May (0.02%. The higher relative condition factor (Kn) recorded inJune (3.23%), estimated the maturation of the gonad of M.ensis. Analysis based on dietary overlaps showed that the M.ensis prawn assemblage comprised 9 food guilds (polychaetes (33 %), sand and mud (16 %), phytoplankton (11.9 %), appendages of crustacean (11 %), plant matter (8.62 %), debris (8%), animal derivative (5%) zooplankton (1.4 %), and unidentified food item (0.43 %). Polychaete is the most dominant food item ingested. On the basis of food composition found in the stomach, it can be conclude that M.ensis is omnivorous.